REVIEW OF THE G.S. KAYMARAZOV’S MONOGRAPH “CULTURAL FORMATION IN AUTONOMOUS REPUBLICS OF THE NORTH CAUCASUS. 1961 – 1980S’. HISTORY. PROBLEMS OF COOPERATION. PART 2” - Mirzabekov, Mirzabek Ahaevic (History, Archeology and Ethnography of the Caucasus, 2019)
A new monograph by the Doctor of Historical Sciences, Professor, Principal Researcher of the Institute of History, Archeology and Ethnography of the Dagestan Scientific Center of RAS Gani Kaymarazov “Cultural Formation in the Autonomous Republics of the North Caucasus. 1961-1980s’. History. Problems of cooperation” has been published. The monograph is a continuation of a two-volume scientific publication, the first part of which was published in 2016. It covers the history of cultural formation in Dagestan, Kabardino-Balkaria, North Ossetia and Chechen-Ingushetia in the 1960-1980s’ in the context of their cooperation and interaction.
Keywords: Kaymarazov Gani Shikhvalievich; cultural formation; monograph; North Caucasus; review.